Analysis of Factors Determining Islamic Motivation Entrepreneuship of Muslim Women Entrepreneurs in Jakarta. - Ellyana Amran; Willy Arafah (Universitas Trisakti, 2020)
The purpose of this study was to analyze the influence of Islamic Leadership on Islamic Motivation Entrepreneurship and the indirect effect of Islamic Leadership on Performance Islamic Business with Islamic Motivation Entrepreneurship as a mediating variable for Muslim women entrepreneurs in Jakarta. The research method used is quantitative method. Research respondents are IWAPI Muslim women entrepreneurs in Jakarta with a sample size of 354 Muslim entrepreneurs. Sample is non probability sampling by using purposive sampling. Data is collected using questionnaire and methods analysed by using Structural Equation Model (SEM). The results showed that there was influence of Islamic Leader on Islamic Business Performance either directly or indirectly through Islamic Motivation Entrepreneurship as mediation. Furthermore there is a positive influence of Islamic Leadership on Islamic Motivation Entrepreneurship; and there is a positive influence of Islamic Motivation Entrepreneurship on Islamic Business Performance.